2017
DOI: 10.1111/liv.13550
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world efficacy and safety of ombitasvir, paritaprevir/r+dasabuvir+ribavirin in genotype 1b patients with hepatitis C virus cirrhosis

Abstract: OBV/PTV/r+DSV+RBV proved to be highly efficient in our population of cirrhotics with a 96.6% SVR. Serious adverse events related to therapy were reported in 61/2070(2.9%), most of them liver decompensation (1.9%), related to hepatic dysfunction, and lower platelet count.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 43 publications
3
23
3
Order By: Relevance
“…10 Beyond clinical trials, numerous studies have evaluated the PTV/r/OBV + DSV combination administered for 12 weeks in clinical practice, all of them including a great proportion of patients with cirrhosis. [11][12][13][14][15][16][17] As a whole, these studies have consistently shown SVR12 rates higher than 95% in all subgroups of patients, confirming data obtained from pivotal clinical trials. A recent meta-analysis evaluating more than 5000 patients from 20 real-world cohorts of 12 different countries has shown SVR12 rates in genotype 1b-infected patients of 98%, with only 2.5% of drug discontinuations and 3.12% of SAEs.…”
supporting
confidence: 67%
“…10 Beyond clinical trials, numerous studies have evaluated the PTV/r/OBV + DSV combination administered for 12 weeks in clinical practice, all of them including a great proportion of patients with cirrhosis. [11][12][13][14][15][16][17] As a whole, these studies have consistently shown SVR12 rates higher than 95% in all subgroups of patients, confirming data obtained from pivotal clinical trials. A recent meta-analysis evaluating more than 5000 patients from 20 real-world cohorts of 12 different countries has shown SVR12 rates in genotype 1b-infected patients of 98%, with only 2.5% of drug discontinuations and 3.12% of SAEs.…”
supporting
confidence: 67%
“…We previously reported a very high rate of HCV SVR in our large cohort of 2070 patients: 96.6% in intention to treat and the SVR reached even 100% in co-infected patients. 22 Even though we reported 2.9% rate of serious adverse events leading to discontinuation of therapy, most of them with liver decompensations (rate 1.9%), we did not have such events in HBV-co-infected patients. 0%-30%, HBV-associated hepatitis; and 0%-30%, necessitating anti-HBV treatment.…”
Section: Discussioncontrasting
confidence: 60%
“…DAA therapy has high success rate (more than 90%) and fewer side effects than the interferon-based regimens. [22][23][24][25][26] The current guidelines for coinfected patients with HCV and HBV recommend that when HCV is replicative, the patient should receive the standard treatment for HCV infection. 27,28 A major concern in the treatment of HBV-HCV co-infection is a "flare-up" of hepatitis due to the risk of HBV reactivation during or after HCV clearance that may increase the risk of liver damage.…”
Section: Introductionmentioning
confidence: 99%
“…In the German cohort, analysis of response across subgroups showed consistently high SVR rates: 95% in patients with cirrhosis (n = 123/129), 100% in those with moderate to severe renal impairment (n = 34/34) and 96% in subgroups that are usually excluded from clinical trials (including patients ≥70 years old [n = 64/67] and prior failures to protease inhibitor treatment [n = 46/48]). The results from a Romanian cohort also confirmed this, reporting an SVR of 96.6% in patients with genotype 1b and cirrhosis receiving ombitasvir/paritaprevir/ritonavir plus dasabuvir, administered with ribavirin …”
Section: Efficacy In the Real‐world Settingmentioning
confidence: 99%